Serving on a Graduate Medical Education Diversity, Equity, Inclusion, and Justice Committee: Lessons Learned From a Journey of Growth and Healing - Kara, Areeba; Wright, Curtis; Funches, Levi; Williamson, Francesca; Hicks, Ralph A.; Sutton, Timothy A.; Nabhan, Zeina (Frontiers in Public Health, 2022)
Efforts towards achieving diversity, equity, inclusion, and justice (DEIJ) within graduate medical education (GME) often begin with the formation of a DEIJ committee that steers the work. Little is known about the experiences and the challenges faced by those serving on such committees. We sought to describe the experiences of members of our institutional GME DEIJ committee to gain knowledge that would propel this work forward. An open-ended survey was electronically administered to members of our institutional GME DEIJ committee. Responses were analyzed using a rapid qualitative analytical approach. Eighteen members (58%) responded. Of these, (67%) were women and five (28%) were Black. Six domains emerged: ‘motivation’, ‘challenges’, ‘emotional response’, ‘highs’, ‘facilitators’, and ‘advice’. Black respondents more often cited the need to increase diversity as a motivator to join this work. Women and Black respondents more often identified time constraints as a challenge to participation. Some members found the work emotionally draining; others described it as uplifting. Two themes emerged as high points of participation-pride and achievement around the work completed and the personal benefits of building a community with a shared purpose. Three themes emerged as facilitators: effective leadership, support, and the psychological safety during the meetings. Many arrived at the realization that change would take time and advocated for patience and perseverance. Protected time and DEIJ expertise were identified as integral to successful committee work. Our findings provide novel insights into the experience of serving on a GME DEIJ committee and highlights infrastructural and institutional prerequisites for success.